How Emotions Influence the Psychophysical Well-being of Children - Manuela Valentini; Roberta Giontarelli (Maria Curie-Skłodowska University, Lublin, Poland, 2022)
Introduction: The current work, through a strict review of the literature, is aimed at highlighting how emotions, physical activity and a healthy diet can affect psychophysical well-being in childhood, particularly between the ages of 3-12. Research Aim: An analysis of research and texts on the relationship between emotions, nutrition, physical activity in pre-school- and school-aged children was performed. The article focuses on an in-depth bibliographic research through the most important search engines by analyzing scientific protocols/articles published from 2010 to 2022 in international journals of the sector. Evidence-based facts: Research is presented on the extent to which emotions can influence psychophysical wellbeing in developmental age including the relationship between emotions and physical activity activity, emotions and nutrition, physical activity and nutrition. Summary: The ability to regulate emotions is of particular importance as it affects the child's educational process, the school context and physical, emotional, cognitive and social well-being. To this end, further investigations are needed to investigate this issue, given the great value it has in the interaction with nutrition and physical activity.